Influence of the use of autogenous bone particles to close the access window after maxillary sinus floor augmentation: an experimental study in rabbits - Giacomo Favero; Jose Viña-Almunia; Carmen Carda; José Javier Martín de Llano; Berta García-Mira; David Soto-Peñaloza; Miguel Peñarrocha-Diago; Daniele Botticelli (SpringerOpen, 2020)
Abstract Aim To study the influence on the healing of the placement of particulate autogenous bone in the antrostomy and in the subjacent region after maxillary sinus elevation. Material and methods Sixteen New Zealand rabbits were undergone to bilateral maxillary sinus floor augmentation with 4 × 4 mm antrostomy dimension. The sinus mucosa was elevated, and the space obtained was filled with xenograft. In the test site (treated sites), autogenous bone was harvested from the tibia and was placed either in the antrostomy and the subjacent region while the control site was left untreated. Antrostomy was covered bilaterally with collagen membranes. Animals were euthanized after 1 and 8 weeks of healing, with 8 rabbits in each group. Histomorphometric evaluations were done. The Wilcoxon test is used for statistical analysis, for a 5% statistical significance. Results After 1 week of healing, the new bone proportion in the antrostomy was 7.7 ± 11.2% and 6.1 ± 6.4% in the treated and untreated sites, respectively. In the subjacent region (close-to-window region), hardly any new bone was assessed. In the elevated region, 2.7-2.8% of total new bone was found in both sites. In the antrostomy region, after 8 weeks of healing, 35.5 ± 20.9% of new bone in the treated sites, and 28.6 ± 24.1% in the untreated sites was observed (p = 0.499). In the close-to-window region, the respective proportions were 25.8 ± 16.1% and 17.6 ± 16.3% (p = 0.018). In the elevated region, the total new bone reached fractions of 27.9 ± 12.9% and 23.6 ± 15.2% in the treated and untreated sites, respectively (p = 0.128). Conclusions The placement of autogenous bone in the antrostomy and the subjacent region after maxillary sinus elevation, slightly enhanced bone formation compared with sites only grafted with xenograft. Though, only the subjacent close-to-window region showed a statistical significance at 8 weeks of healing. Despite the limitations of the present study, due to its preclinical nature, findings should be extrapolated to humans with caution.